Zdravljenje erektilne disfunkcije in prezgodnje ejakulacije - Ferk, Polonca (Farmacevtski vestnik, 2015)
Erectile dysfunction and premature ejaculation are the most common male sexual disorders and an increasing health problem in developed countries. Etiopathogenesis of the two disorders is multifactorial and includes several biological and psycological factors. Pharmacological, psychological and/or surgical treatment approaches depend on the type and severity of the disorder. Phosphodiesterase type 5 inhibitors are the drugs of choice in pharmacotherapy of erectile dysfunction. At present, dapoxetine, a short-acting selective serotonin reuptake inhibitor, is the only drug indicated to treat premature ejaculation. Several promising therapeutic approaches for treating male sexual dysfunction are being investigated, including stem cells and gene therapy.
Keywords: erectile dysfunction; erektilna disfunkcija; premature ejaculation; prezgodnja ejakulacija; farmakoterapija; pharmacotherapy; phosphodiesterase type 5 inhibitors; zaviralci fosfodiesteraze tipa 5; dapoksetin; dapoxetine